From resistance to persistence: Insights of a mathematical model on the indiscriminate use of insecticide - Schechtman, Helio; Valle, Denise; Souza, Max O. (PLOS Neglected Tropical Diseases, 2020)
Author summary Mosquitoes populations are typically very large, and the fraction of insecticide resistant individuals in these populations has been observed to be increasing in recent field measurements. This is commonly attributed to the indiscriminate use of insecticides, but it also suggests that small fitness costs might also come into play. Using a mathematical model for the mosquito population, we study the impact of different application policies on the development of resistance in a population that was initially almost completely susceptible. We focus on two different policies: one that can be associated with a more restrained public policy, and a more permissive that is typically found in gated communities. The results suggest that a more permissive use not only increases the fraction of resistant individuals in the population, but might also lead to the replacement of a susceptible population by a resistant one. They also show that, while such a permissive policy initially brings down the overall mosquito population, the development of resistance claims its price and it diminishes the efficacy of insecticide control in the long term scenario. While this is perhaps an oversimplified model to be used quantitatively, it captures enough of the qualitative underlying biological and ecological features, and foster further discussions and studies on this issue.